2016
DOI: 10.1002/gps.4536
|View full text |Cite
|
Sign up to set email alerts
|

Trends in patterns of antidepressant use in older general population between 2006 and 2012 following publication of practice guidelines

Abstract: While treatment duration and biological monitoring were often inadequate in older patients, the publication of guidelines by the French health regulatory authorities did not lead to any significant and sustained improvement in their patterns of antidepressant use. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Reduced efficacy or higher toxicity due to interindividual variability contributes to treatment failure or noncompliance. Approximately 62% of the depressive patients were reported to show no effective response to their treatment …”
Section: Highlights Of Ethnic Differences On Allele Frequencies Of Mamentioning
confidence: 99%
“…Reduced efficacy or higher toxicity due to interindividual variability contributes to treatment failure or noncompliance. Approximately 62% of the depressive patients were reported to show no effective response to their treatment …”
Section: Highlights Of Ethnic Differences On Allele Frequencies Of Mamentioning
confidence: 99%
“…9 With the increasing research focus on knowledge translation (KT) and evidence-based medicine (EBM), and the growing importance of the uptake of best evidence into clinical practice, ITS analysis has become a common tool used in assessing the effect of clinical practice guidelines and recommendations. [10][11][12][13][14] For instance, ITS design was used to look at de-adoption of tight glycemic control in critically ill patients across 113 intensive care units (ICUs) in the USA following publication of a randomized trial showing that tight glycemic control can increase mortality. 15 In another study, ITS design was used in evaluating the impact of Otolaryngology Head and Neck Surgery (OHNS) guidelines on perioperative care process and patient outcomes in children undergoing tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that only a minority of affected patients is actually treated and that treatment duration is frequently inadequate. 9,14,15 However, it was also reported that antidepressants are often used without justification and that antidepressant prescriptions may be influenced by social factors such as loneliness or by the presence of somatic comorbidities. [16][17][18] A recent review of seniors aged 55 years and older found antidepressant use in only 20% to 45% of persons with depression.…”
Section: Introductionmentioning
confidence: 99%